Perceived Usefulness as Correlate of Undergraduate Students' Patronage of Online Public Access Catalog in South-West Nigeria. Issue 5 (3rd July 2020) - Odunola, Oluwole Akanmu; Tella, Adeyinka
Abstract: This study investigated the correlation of perceived usefulness and patronage of the Online Public Access Catalogs (OPACs) by undergraduate students in universities in South-west Nigeria. The descriptive research design of the ex post facto was adopted using a sample of 1, 527 selected from the total population of 239, 048 undergraduate students in the universities. A questionnaire was used to collect the data. The results revealed that most undergraduate students patronized the OPAC two to three times a week. The findings show that the perceived usefulness of the OPAC had influence on its patronage by undergraduate students in the universities (r = 0.516**, N = 1333, P < 0.05). The study concluded that perceived usefulness influenced OPAC patronage by undergraduate students in the universities. The study, therefore, recommends that the importance of the OPAC should be emphasized in the library to enhance its perceived usefulness by the students in the university libraries.